PEMANTAUAN KAWASAN SABUK HIJAU WADUK WADASLINTANG MENGGUNAKAN CITRA SATELIT LANDSAT 8 - , ERLYNA NOUR ARROFIQOH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Wadaslintang reservoir is a multipurpose dam that built in Central Java. The volume and rate of operations on the wane due to the high rate of sedimentation. To ensure optimum function of the reservoir and sustainable management activities should be focused on security and rescue efforts as well as the area surrounding the reservoir. Vegetated areas, especially the green belt, should be protected and should remain preserved. One of the efforts to control landuse in the reservoir area is to monitor green belt and determine land use around the reservoir. Reducing land area of vegetation, will have negative impacts on the hydrological cycle of the reservoir. To monitor green belt and land use around the Wadaslintang reservoir using satellite remote sensing data was done by comparing the Landsat 7 ETM+ in 2001 and Landsat 8 in 2013. The method used in this research is the digital classification using maximum likelihood to determine land use. The results are then analyzed to detect the land use and the green belt that changes over 12 years. Based on the accuracy test showed that the maximum likelihood method can be used to create a land use map with overall accuracy Landsat 7 ETM+ in 2001 is 89,14% and Landsat 8 in 2013 is 93,43%. Analysis of the classification results proved that there are land use changing on the green belt area, forest decreased 60.300 m 2 , agriculture field increased 145.800 m 2 , water increased 581.400 m 2 , dry agriculture decreased 775.800 m 2 , cropland increased 286.200 m 2 , shrub decreased 338.400 m 2 , and urban area increased 161.100 m 2 .